Strategy of Developing Tomini Bay for Economic Growth of Coastal Community in Central Sulawesi - Muzakir, Muzakir; Suparman, Suparman (Semarang State University, 2016)
This research aims to analyze the potential and the strategy of developing Tomini Bay to improve the economic growth of the coastal community in Central Sulawesi. The research is located in four regencies in Central Sulawesi. The method uses the descriptive analysis using SWOT analysis. The research result shows that the potential of fisheries resources in Poso Regency, Parigi Moutong Regency, Tojo Una-Una Regency, and Banggai Regency can support the development of Tomini Bay region based on fisheries in order to accelerate the economic growth of coastal communities in Central Sulawesi. The potential fishery resources that can support the development of Tomini Bay area are the potential of fisheries, marine and coastal infrastructure, social economy and geographic conditions in four regencies. The strategies are building the marketing network for fishery products both the catching and cultivation, improving the fishery human resouce capacity, controlling the fishery product quality, and increasing the social awareness to maintain the ecosystem sustainability. To optimize the utilization of Tomini Bay, it is suggested to improve the involvement of the regional government, the central government, and also the private sector and the whole community.